2020
DOI: 10.1061/(asce)nh.1527-6996.0000409
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Impacts of the COVID-19 Pandemic: Statewide Analysis of Social Separation and Activity Restriction

Abstract: The COVID-19 pandemic resulted in significant social and economic impacts throughout the world. In addition to the health consequences, the impacts on travel behavior have also been sudden and wide ranging. This study describes the drastic changes in human behavior using the analysis of highway volume data as a representation of personal activity and interaction. Same-day traffic volumes for 2019 and 2020 across Florida were analyzed to identify spatial and temporal changes in behavior resulting from the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 24 publications
3
88
0
2
Order By: Relevance
“…Dramatic decreases in traffic have been noted in NYC 17 and many other places [18][19][20][21] in response to the pandemic, including Padova, Italy 18 and Auckland, New Zealand. 19 The study in Padova found a decrease in traffic flow (vehicle counts per unit time) in 2020 of approximately 70%, compared to 2018-2017.…”
Section: Discussionmentioning
confidence: 99%
“…Dramatic decreases in traffic have been noted in NYC 17 and many other places [18][19][20][21] in response to the pandemic, including Padova, Italy 18 and Auckland, New Zealand. 19 The study in Padova found a decrease in traffic flow (vehicle counts per unit time) in 2020 of approximately 70%, compared to 2018-2017.…”
Section: Discussionmentioning
confidence: 99%
“…With the establishment of the "new normal," new trends were seen with emergency department (ED) admission rates. A notable trend was the decrease in automobile traffic volume that was seen nationally [1], which led to reports of fewer traffic accidents throughout states such as Florida and Missouri [2], and internationally in Turkey and Australia [1,3,4]. Concurrently, the lockdowns have led to decreased number of trauma cases [5][6][7] by 57.4% [8], contributing to a decrease in the volume of neurosurgical care by 40% [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These changes have resulted both from fear of getting sick and from restrictions imposed by government. Parr et al (2020) found that in Florida while the decrease in mobility was triggered by emergency orders, business closures, online schooling and reduced social activities led to freeway traffic declining by 52.4% and arterial volumes by 40.5% compared to 2019. Social distancing orders and curtailment of non-essential travel were common restrictions implemented by many state and local governments throughout the United States and the rest of the world ( Kim et al, 2021 ).…”
mentioning
confidence: 99%